Evaluation of nutritional status of recently hospitalized patients - Khattak, Muhammad Muzaffar Ali Khan; Khan, Alam; Begum, Shagufta; Abid, Javeria; Qadir, Syed Saeed (Asian Network for Scientific Information, 2002)
Three hundred and fifty five patients of various age groups were assessed for their nutritional status. Among these patients, 65 were children, 166 adult male, and 124 adult female. In children all the anthropometric parameters were lower than the reference values with the exception for age group 6.1 – 10.0 years, whose weight were more than the reference values. Hundred percent mal-nourishment was observed in male adults. All the parameters i.e. weight, upper mid arm circumference (UMAC), triceps-skinfolds (TSF) hemoglobin and blood sugar were lower than the reference values. The data collected for female adults also indicated that the females were hundred percent mal-nourished as well with the exception 51+ years of age whose weights were more than the respective standards or reference values. This study indicates the gravity of the problem of mal-nourishment that exists in the hospitalized patients. Therefore, there is an urgent need for the nutritional assessment/intervention in the hospitalized patients.